Comparative simulation study of electric motors for high performance of 3D printers - Mhamed El Mrabet; Zineb Mekrini; Abdelilah El Mesbahi; Mohammed Boulaala (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
3D printing is a process in which material is joined layer by layer under computer control to make a 3D object easy to get almost any shape. This technology finds applications in various fields and it is attracting considerable interest from industry and academia. There are many different brands and models of motors used in 3D printers, and they all vary in quality and effectiveness. In this article we present the principal of the 3D printer, types of motors used in 3D printer and mathematical modelling of this motors like brushless direct current (DC) motor, permanent magnet synchronous motor (PMSM), and stepper motor. The models of analytical equations describing the three systems of motors are evaluated and developed by Matlab/Simunlink. In this paper, we have conducted a comparison of the series of results from simulation between the performance of PMSM, brushless DC and stepper motor. Among several criteria, this simulation study allows to select the criterion of response time to reach the desired speed and the precision of the rotor position to choose the most performant motor for 3D printers.